2019
DOI: 10.7762/cnr.2019.8.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bread with Nigella Sativa on Blood Glucose, Blood Pressure and Anthropometric Indices in Patients with Metabolic Syndrome

Abstract: Nigella sativa ( N. sativa ) is one of important herbal foods in traditional medicine and many studies have conducted to show the effects of this plant on several diseases. The goal of this study was the evaluation of effects of bread with N. Sativa on clinical parameters such as blood glucose, blood pressure (BP) and anthropometry indices in subjects with metabolic syndrome (MetS). A study as double-blind, cross-over, randomized clinical trial was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
(29 reference statements)
0
24
0
Order By: Relevance
“…Conversely, a recent cross-over study (2 months treatment, 2 weeks washout period) evaluated the effects of N. sativa , as a form of traditional bread spiked with seeds (2 g), on FBG, BP and anthropometric indices (BW, waist circumference or WC, and BMI body mass index) in patients with metabolic syndrome. It found no significant effect between the mean of changes of parameters in the beginning and end of study (time effect), with the exception of diastolic BP ( Mohtashami, 2019 ).…”
Section: Health-promoting Effects: Clinical Trials In Humansmentioning
confidence: 85%
“…Conversely, a recent cross-over study (2 months treatment, 2 weeks washout period) evaluated the effects of N. sativa , as a form of traditional bread spiked with seeds (2 g), on FBG, BP and anthropometric indices (BW, waist circumference or WC, and BMI body mass index) in patients with metabolic syndrome. It found no significant effect between the mean of changes of parameters in the beginning and end of study (time effect), with the exception of diastolic BP ( Mohtashami, 2019 ).…”
Section: Health-promoting Effects: Clinical Trials In Humansmentioning
confidence: 85%
“…MetS patients consuming 3 g powdered N. sativa daily in 100 g bread for 2 months did not exhibit significant decreases in FBG. 17 In the second study, fenugreek administered as a single serving of 56 g of bread containing 2.8 g fenugreek failed to significantly affect PPBG in eight diet-controlled diabetics, although a decrease in insulin secretion over 2 h versus placebo was reported. 25 …”
Section: Discussionmentioning
confidence: 96%
“…A lack of hypotensive effect in T2D subjects was also reported for a polyherbal encapsulated formulation of N. sativa and fenugreek that additionally contained Allium sativum , Aloe vera , P. psyllium , and S. marianum administered over 40 days. 29 Using a food matrix consisting of 100 g bread containing 3 g N. sativa powder, Mohtashami 17 reported no effect on SBP or DBP in 51 subjects with MetS, who consumed the formulated bread for 2 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained during this study ( Table 5 ) on the level of serum glucose of chickens are in agreement with recent reports [ 29 , 40 ] but in disagreement with other reports [ 41 , 42 ]. Some controversial observations could be explained where the type of the extract, whole seed, and duration of consumption may exert different effects on glucose level as has been observed by Mohtashami [ 60 ] who reported that N . sativa did not significantly affect the fasting blood glucose level but significantly decreased its levels during oral glucose tolerance test (OGTT) when compared to diabetic control by affecting the time course of glucose absorption from the intestine.…”
Section: Discussionmentioning
confidence: 99%